Temporary Migration and Endogenous Risk Sharing in Village India - Morten, Melanie (Journal of Political Economy, 2019)
When people can self-insure via migration, they may have less need for informal risk sharing. At the same time, informal insurance may reduce the need to migrate. To understand the joint determination of migration and risk sharing, I study a dynamic model of risk sharing with limited commitment frictions and endogenous temporary migration. First, I characterize the model. Second, I structurally estimate the model using the new ICRISAT panel from rural India. Third, I introduce a rural employment scheme. The policy reduces migration and decreases risk sharing, lowering the welfare gain of the policy.